Myelosuppression after frontline fludarabine, cyclophosphamide, and rituximab in patients with chronic lymphocytic leukemia: Analysis of persistent and new‐onset cytopenia. Issue 21 (13th August 2013) - Strati, Paolo; Wierda, William; Burger, Jan; Ferrajoli, Alessandra; Tam, Constantine; Lerner, Susan; Keating, Michael J.; O'Brien, Susan
Abstract : BACKGROUND: The combination of fludarabine, cyclophosphamide, and rituximab (FCR) has produced improved response rates and a prolonged survival in patients with chronic lymphocytic leukemia (CLL). However, its therapeutic power is counterbalanced by significant hematologic toxicity. Persistent and new‐onset cytopenia after the completion of FCR raise concern about disease recurrence, the development of therapy‐related myeloid malignancies (TRMM), and infections. METHODS: A total of 207 patients with CLL who achieved complete response, complete response with incomplete bone marrow recovery, or nodular partial remission were analyzed after frontline FCR therapy. RESULTS: Three months after the completion of therapy, 35% of patients had developed grade 2 to 4 cytopenia (according to Common Terminology Criteria for Adverse Events [version 4.0]). Factors found to be associated with cytopenia at 3 months after therapy were older age, advanced Rai stage disease, and lower baseline blood counts. Moreover, patients with cytopenia were less likely to have completed 6 courses of therapy with FCR. At 6 months and 9 months after therapy, the prevalence of grade 2 to 4 cytopenia was 24% and 12%, respectively. No differences in progression‐free survival and overall survival were noted between cytopenic and noncytopenic patients or between patients with persistent and new‐onset cytopenia. The prevalence of TRMM was 2.3% and did not differ significantly between cytopenic and noncytopenic patients or between those with persistent and new‐onset disease. Late infections were more common in patients who were cytopenic at 9 months (38%) and were mostly bacterial (67%). CONCLUSIONS: Cytopenia after the completion of therapy is a common complication of frontline FCR that improves over time, particularly for new‐onset cases. The presence of persistent cytopenia (lasting up to 9 months after the completion of therapy) should not raise concern about CLL recurrence of the development of TRMM, but should encourage surveillance for bacterial infections for an additional 9 months. Cancer 2013;119:3805–3811. © 2013 American Cancer Society. Abstract : Persistent and new‐onset cytopenia after the completion of therapy are a common complication of frontline therapy with fludarabine, cyclophosphamide, and rituximab. Although their presence does not raise concerns about chronic lymphocytic leukemia recurrence or the development of therapy‐related myeloid malignancies, it should encourage surveillance for bacterial infections.